2014
DOI: 10.1021/ja5084267
|View full text |Cite
|
Sign up to set email alerts
|

Helical Gold Nanorods as Chiral Recognition Nanostructures: A Relativistic Density Functional Theory Study

Abstract: We establish helical gold nanorods as the first examples of chiral recognition nanostructures by examining the simple chiral molecule CClHDT adsorbed on the helical Au40 nanorod. We calculate the vibrational circular dichroism (VCD) spectra of the R and S enantiomers of CClHDT adsorbed on the R (or S) enantiomer of Au40 using relativistic density functional theory. The highest adsorption energy is found when the Cl atom of CClHDT binds to a low-coordinated Au atom at the edge of Au40. There are three adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…2 ). The absorbance decrease at 620 nm was due to the aggregation of AuNRs 41 . Furthermore, the mixture solution of AuNRs and L- or D-Gln was centrifuged for 5 min at 1145 × g. As shown in Figure S 2 , some gray precipitate could be observed on the side wall of the tube, which contained D-Gln and AuNRs; no obvious change was found in the tube of L-Gln–AuNRs under the same experimental condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). The absorbance decrease at 620 nm was due to the aggregation of AuNRs 41 . Furthermore, the mixture solution of AuNRs and L- or D-Gln was centrifuged for 5 min at 1145 × g. As shown in Figure S 2 , some gray precipitate could be observed on the side wall of the tube, which contained D-Gln and AuNRs; no obvious change was found in the tube of L-Gln–AuNRs under the same experimental condition.…”
Section: Resultsmentioning
confidence: 99%
“…We infer that in this work the chiral recognition is the direct consequence of the intrinsical chirality of AuNRs. Metal surface exhibits the inherent chiral structure 50 , and Au nanoparticles or AuNRs can also exhibit intrinsic chirality 26 , 40 , 41 , 51 53 . In 2012, Bürgi group first gave the CD spectrum of Au clusters capped with the achiral ligand, which is the spectroscopic evidence for intrinsic chirality of Au cluster 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a density functional theory (DFT) study, we showed that segments of the (7, 3) single-walled nanotube with a central linear strand, Au 24 , Au 32 , and Au 40 , are stable as free-standing structures and represent atomic cluster analogues of the helical gold wires . That is, they are local minima on the potential energy surface which are robust in the sense that they remain stable when a variety of species are adsorbed on them. , However, they have undercoordinated gold atoms at their ends and, at room temperature, ab initio molecular dynamics calculations indicate that they transform to compact core–shell structures . In this study, we extend these nanorods to include Au 48 and Au 56 and focus on their optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, understanding the mechanism of chiral recognition, and then pursuing the larger gap between two enantiomers and more efficient chiral electrode materials to develop the application of chiral PEDOT is valuable and fascinating. On the other hand, to date, the dominant approaches for chiral recognition are chromatographic methods (including high performance liquid chromatography (HPLC), [38][39][40] gas chromatography (GC), [41][42][43] chiral ligand exchange chromatography (CLEC), 44 and supercritical uid chromatography (SFC) 45,46 ), spectroscopic characterizations (including uorescence detection (FL) 47,48 and vibrational circular dichroism (VCD) 49 ), capillary electrophoresis (CE) 50,51 and molecular imprinting polymer techniques (MIP). 52,53 Even if these techniques are fairly efficient, they are usually time consuming, require costly equipment and need sophisticated and extensive analysis procedures.…”
Section: Introductionmentioning
confidence: 99%